Gabriel Finley & the raven's riddle - Hagen, George, 1958- (Yearling, 2016)
Eleven-year-old Gabriel, with the help of the young raven Paladin, which whom he has a magical bond, travels to the foreboding land of Aviopolis, where he must face challenges and unanswerable riddles to rescue his long-missing father.